Uso del dinero electrónico y su relación con la salud financiera de las familias de la ciudad de Loja - Jaramillo Roblez, Grace Geomira (2024)
At present, electronic money is booming, because it has become a powerful tool that has transformed the way financial transactions are carried out and, in turn, has become a variable in the financial health of society, as it has changed the way money is managed. It has also become a variable in the financial health of society, as it has changed the management of money and also marked leaks of money such as ant-spending, which are unfamiliar terms for the population. However, in personal finance it is of vital importance to know and recognise them. Financial health is understood as the ability to control income and meet expenses, without neglecting savings for the future. The general objective of the research was to determine the use of electronic money and its relationship with the financial health of the residents of the city of Loja, which in turn leads to the construction of a financial self-assessment tool, with which decisions can be made and financial health can be strengthened. The methodology used had a mixed approach of cross-sectional design, correlational scope, using the chi-square test and its measures of association PHI and Crammer's V to determine the dependence of the variables and based on the measures of association based on chi-square of the strength of association of the same, likewise the research is of a non-experimental type applied, since based on the results the barometer is structured; The population under study are the resident families of the city of Loja, in a sample of 382 families, allowing to know the levels of use of electronic money and to determine the state of financial health, revealing that people with a higher educational level have greater knowledge in the financial sphere, in addition that, in women there is a greater tendency of ant expenses and a lower financial health in contrast with the male sex.